Feasibility study for the design of a wastewater treatment plant with effluent from the main rainwater canal No. 37 located in the Tarqui parish of Guayaquil canton - Zalamea Cedeño, Janeth Katherine; Palacios Flores, Jefferson Segundo (Ingeniería Química y Desarrollo, 2022)
About 80 - 85% of the global pollution is a product of human activities; the pollution that the open rainwater canals in the north of Guayaquil, which collect effluents from 558 hectares and a channel of 8.64 km that starts in the upper part of the sector known as Flor de Bastión, to finally discharge into the Daule River. The channels are in a very poor state, with unhealthy conditions, bad odors, insect proliferation, loss of biodiversity, and siltation, the most affected being the receiving body, which casts doubt on the capacity of this body of water to purify itself over time. To evaluate the effluent, a sample was taken at the end of the concrete-lined open trapezoidal canal called "Canal No. 37", followed by its characterization in terms of physical and chemical parameters; it does not comply with the maximum permissible limits for discharge into a freshwater body, and the implementation of a wastewater treatment plant is considered a corrective solution.
Keywords: Main canal; pollution; effluent; Wastewater treatment plant (WWTP); Receiving body